Independensi dan Urgensi Restrukturisasi Sistem Peradilan Pidana Indonesia Berdasarkan Aspek Kekuasaan Kehakiman - Rico Yodi Tri Utama; Retno Saraswati (Ajudikasi : Jurnal Ilmu Hukum, 2021)
Settlement of crimes by the criminal justice subsystem as a whole often does not run optimally. The position of the subsystems that are under the executive branch is sometimes used as a tool by the authorities to achieve their political goals regardless of the prevailing legal principles. This study aims to provide an overview of the position and function of criminal justice subsystems and focuses on finding the ideal system concept so that the implementation of an independent criminal justice system can be optimally realized by implementing a systems approach and restructuring the legal system. This study uses a normative juridical research method with a statute approach which is studied using a descriptive analysis. Based on the research results, the components of the criminal justice subsystem seem separate from one another, giving rise to sectoral egos and not yet showing the independence of each criminal justice subsystem. On that basis, to create an integrated, free and independent criminal justice system without any influence from power, it must provide a clear space for judicial independence (judicial power), thus placing the Supreme Court as the supervisor and controller of the entire criminal law enforcement process. The criminal justice subsystems must be under one door, not fragmented in other state institutions so that it is hoped that these subsystems can work optimally and be free from the influence of power.